Β‐AgVO3 Nanorods as Peroxidase Mimetic for Colorimetric Determination of Glucose. Issue 7 (13th June 2017) - Lu, Junyu; Wei, Lianqiang; Yao, Dongmei; Yin, Xiuju; Lai, Hongfang; Huang, Xiuxiang
Abstract : β‐AgVO3 nanorods have been demonstrated to exhibit intrinsic peroxidase‐like activity. The oxidation of glucose can be catalyzed by glucose oxidase (GO x ) to generate H2 O2 in the presence of O2 . The β‐AgVO3 nanorods can catalytically oxidize peroxidase substrates including o ‐phenylenediamine (OPD), 3, 3′, 5, 5′‐tetramethylbenzidine (TMB), and diammonium 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonate) (ABTS) by H2 O2 to produce typical color reactions: OPD from colorless to orange, TMB from colorless to blue, and ABTS from colorless to green. The catalyzed reaction by the β‐AgVO3 nanorods was found to follow the characteristic Michaelis–Menten kinetics. Compared with horseradish peroxidase and AgVO3 nanobelts, β‐AgVO3 nanorods showed a higher affinity for TMB with a lower Michaelis–Menten constant ( K m ) value (0.04118 mM) at the optimal condition. Taking advantage of their high catalytic activity, the as‐synthesized β‐AgVO3 nanorods were utilized to develop a colorimetric sensor for the determination of glucose. The linear range for glucose was 1.25–60 μM with the lower detection limit of 0.5 μM. The simple and sensitive GO x ‐β–AgVO3 nanorods–TMB sensing system shows great promise for applications in the pharmaceutical, clinical, and biosensor detection of glucose. Abstract : Small β‐AgVO3 nanorods with high catalytic activity were synthesized. Then, a simple, cheap, and selective colorimetric sensing method for the determination of glucose in human serum samples was developed based on the peroxidase‐like activity of β‐AgVO3 nanorods. The linear range for glucose was 1.25–60 μM with the lower detection limit of 0.5 μM.